PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN DENGAN KEPERCAYAAN DIRI DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI PEMODERASI - Wijayanthi, Putu Kartika; Widanaputra, A.A. G.P. (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
The purpose of this study was to determine the influence of self confidence and uncertainty of the environment on the relationship between budgetary participation and budgetary slack. This research was conducted at the five-star hotel in Nusa Dua. The sampling method used is purposive sampling with criteria managers holding positions as middle managers (department head) and has held his post for at least one year. The samples used were as many as 12 hotels with a total number of respondents was 108 middle managers. Data collected by using a questionnaire. The data analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the analysis showed that the self confidence and the uncertainty of the environment is not as moderating variables that affect budgetary participation and budgetary slack.
Keywords: Budgetary Slack, Budgeting Participation, Self Confidence, Environmental Uncertainty